Exploring dietary patterns and their association with environmental sustainability and body mass index in children and adolescents: Insights from the National Food, Nutrition and Physical Activity Survey 20152016 - Teixeira, B. (2024)
Objective: To adapt four dietary patterns for children and adolescents, and study their associations with sustainability (greenhouse-gas emissions-GHGE and land use-LU), and health (body mass index-BMI) indicators. Research methods & procedures: Dietary intake of children (3-9y) and adolescents (10-17y) from the National Food, Nutrition and Physical Activity Survey 20152016, Portugal (n = 1153) was assessed through two non-consecutive interviews: one-day food diaries (children), and 24-h recalls (adolescents), using an automated multiple-pass method, including a picture book for portion sizes estimation. Adherence to the Eat-Lancet and World Health Organization (WHO) recommendations, Mediterranean and Atlantic diets were evaluated using adapted versions for pediatrics of the World Index for Sustainability and Health (WISH), Diet Quality Index (DQI), Mediterranean Diet Score (MDS) and Southern-European Atlantic Diet (SEAD), respectively. Diet-related GHGE and LU were estimated using the SHARP-Indicators database. BMI (measured) z-scores were classified according to WHO criteria. A standardized weighted health-sustainability composite index was created (BMI + 0.5*GHGE+0.5*LU). Adjusted linear regression models were computed. Results: WISH, DQI, MDS, and SEAD had weighted mean scores (range) of 50 (0130), 24 (936), 20 (832), and 17 (832), respectively. All dietary patterns were associated with lower environmental impact, particularly in children, but not with BMI. Only MDS explained both health and sustainability indicators in childhood (composite index: sd.ß = 0·223,95%CI:-0·347,-0·072,R2 = 25.1 %), and adolescence (composite index: sd.ß = 0·159,95%CI:-0·315,-0·003,R2 = 31.3 %). Conclusion: The Mediterranean diet was the most related to (higher) environmental sustainability and (lower) BMI. However, in children (not adolescents), the WISH, DQI, and SEAD showed then same associations. (c) 2024 The Authors